(untitled) (Eurasian Medical Research Periodical, 2022)
This study focuses on evaluation of the effect of GERD on eustachian tube function in OSA patients Where 50 patients were collected from different hospitals in Baghdad Iraq, where this study aimed at Evaluation of the effect of GERD on eustachian tube function in OSA patients. The patients were divided into four groups: the control group, which included ten patients, the OSA group, which included 15 patients; the GERD group, which included 15 patients; and the OSA + GERD group, which included ten patients. A statistically significant relationship was found between the four groups, and there were significant differences with the control group when compared.